Essential Oil Constituents of Alpinia scabra and Alpinia murdochii, Two Wild Highland Species from Peninsular Malaysia and Their Anti-Microbial Activity - Syamsir, Devi Rosmy; Tohar, Norsita; Ibrahim, Halijah; Mohamad Ali, Nor Azah; Mokhtar, Mastura; Sivasothy, Yasodha; Awang, Khalijah (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study investigates the chemical constituents of essential oils and their anti-microbial activity of Alpinia scabra and Alpinia murdochii, two wild Zingiberaceae species. The essential oils were obtained by hydrodistillation and the chemical components of the oils were determined by GC-FID (retention indices, RI) and GC/MS analysis. The major components of Alpinia scabra rhizome oil are γ-selinene (33.45%), α-selinene (3.64%) and α-terpineol (3.55 %) while the major components of the leaves are β-pinene (63.37%), α-pinene (6.58 %) and borneol (3.20 %). The major compounds of Alpinia murdochii rhizome oil are γ-selinene (15.51 %), (E,E)-farnesyl acetate (6.56 %), terpinen 4-ol (5.58 %) and α-terpineol (5.04 %). The monoterpenes; β-pinene (23.83 %), sabinene (23.76 %) and terpinene-4-ol (10.49 %) were the major components in the leaf oil of A. murdochii. The lowest MIC values were recorded for the rhizome essential oils of both Alpinia species against all Staphylococcus aureus strains (coded as MSSA, MRSA, Sa7, VISA24, VRSA156) with MIC values ranging from 0.04 mg/mL to 2.50 mg/mL. The rhizome oils of both species also showed a broad spectrum of anti-microbial activity as compared to the leaf oils. © 2020 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.